2018
DOI: 10.1111/bcp.13493
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of parenteral iron in children with inflammatory bowel disease

Abstract: Objectives: Iron deficiency anemia (IDA) frequently complicates inflammatory bowel disease (IBD) in children and adults. Oral iron may exacerbate gastrointestinal symptoms and absorption may be insufficient in intestinal inflammation. Even where oral iron is successful, repletion of iron stores can be unacceptably slow. Intravenous (IV) iron compounds were in the past associated with serious adverse reactions and historically were considered a last resort in children. New generation preparations have a safer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…Following FCM infusion as a single dose of 15 mg/kg up to 1000 mg over 15-20 min, 64% of patients with IDA had resolution of anemia, with 81% showing resolution for ID without anemia [175]. Similar data have been reported by other authors [176,177]. CD (and, for that matter, any other disease causing villous atrophy) is a classic scenario where the results of oral iron replacement are poor due impaired absorption inherent to mucosal injury.…”
Section: Intravenous Iron In Childrensupporting
confidence: 77%
“…Following FCM infusion as a single dose of 15 mg/kg up to 1000 mg over 15-20 min, 64% of patients with IDA had resolution of anemia, with 81% showing resolution for ID without anemia [175]. Similar data have been reported by other authors [176,177]. CD (and, for that matter, any other disease causing villous atrophy) is a classic scenario where the results of oral iron replacement are poor due impaired absorption inherent to mucosal injury.…”
Section: Intravenous Iron In Childrensupporting
confidence: 77%
“…No adverse reactions to treatment were reported. More recently, two studies confirmed the previously observed efficacy and safety data of new-generation IV iron formulations in pediatric patients with IBD [37,56]. Stein et al [37] retrospectively reviewed the charts of all pediatric patients with IBD receiving iron sucrose infusions for IDA at a single center between 2011 and 2015.…”
Section: Which Methods Of Iron Supplementation To Usementioning
confidence: 72%
“…Adverse effects were reported in 18.1% of subjects and 6.6% of infusions, none of which life-threatening or requiring hospitalization. The retrospective and single-center study by Papadopoulos et al [56] analyzed the safety and efficacy outcomes of 41 children with IBD (mostly [56%] with UC) who received parenteral iron (ferric carboxymaltose, n = 35; iron sucrose, n = 7; both, n = 1) over 38 months and showed a mean 2.5 g/dL, 8.4 g/dL, and 16.2% increase of Hb, iron levels, and transferrin saturation, respectively. Three children developed mild rash after infusion, which resolved quickly with chlorphenamine.…”
Section: Which Methods Of Iron Supplementation To Usementioning
confidence: 99%
“…Whereas, historically, high-molecular-weight intravenous iron compounds were burdened by a significant rate of side effects and therefore underused due to safety concerns, the introduction of low-molecular-weight formulations led to a significant decrease in adverse effects [ 85 ]. Various studies performed in children and adolescents with IBD reported a high efficacy of intravenous iron formulations with a relatively low rate of adverse events [ 86 , 87 , 88 , 89 ]. Mamula et al [ 86 ] reported their retrospective experience with intravenous iron dextran infusions in 70 children affected by IBD.…”
Section: Nutritional Assessment and Supplementationmentioning
confidence: 99%